Prevalence of genetic variants in SERPINB2 and PKNOX1 genes in erythema nodosum leprosum patients from southern Brazil - Perazzoli, Simone; Fiuza, Miriãn FM; de Moraes, Paulo Cezar; Heck, Renata; Vianna, Fernanda SL; Bonamigo, Renan R (The Journal of Infection in Developing Countries, 2025)
Introduction: Erythema nodosum leprosum (ENL) is a humoral immune response to Mycobacterium leprae that is characterized by erythematous nodules, and may or may not be associated with systemic symptoms. Thalidomide is the primary treatment for ENL in Brazil, but peripheral neuropathy (PN) is a significant adverse effect. Genetic variants in SERPINB2 and PKNOX1 genes have been implicated in the predisposition to develop thalidomide-induced peripheral neuropathy (TiPN) in patients with multiple myeloma. This study evaluated the prevalence of the polymorphisms in SERPINB2 and PKNOX1 in ENL patients. Methodology: A cross-sectional study was conducted in a sample of ENL patients from southern Brazil to assess the presence of genetic variants of SERPINB2 and PKNOX1. Results: Forty-seven patients with ENL were included. The prevalence of SERPINB2 (rs6103) was 66% for the C allele and 34% for the G allele, and the prevalence of PKNOX1 (rs2839629) was 75% for the A allele and 25% for the G allele. There was significantly relevant presence of the PKNOX1 (rs2839629) A allele in patients with ENL (p < 0.001). In the case of patients with PN, the presence of the C genotype for rs6103 (SERPINB2) was 85% in homozygosity and 77.3% in heterozygosity; and the presence of the A genotype for rs2839629 (PKNOX1) was 84% in homozygosity and 80% in heterozygosity. Conclusions: Polymorphisms in SERPINB2 and PKNOX1 were identified in patients with ENL, with emphasis on PKNOX1. If confirmed by more robust future studies, these findings may guide clinical decisions and treatment guidelines for ENL.